2013
DOI: 10.1371/journal.pone.0076613
|View full text |Cite
|
Sign up to set email alerts
|

Fodrin in Centrosomes: Implication of a Role of Fodrin in the Transport of Gamma-Tubulin Complex in Brain

Abstract: Gamma-tubulin is the major protein involved in the nucleation of microtubules from centrosomes in eukaryotic cells. It is present in both cytoplasm and centrosome. However, before centrosome maturation prior to mitosis, gamma-tubulin concentration increases dramatically in the centrosome, the mechanism of which is not known. Earlier it was reported that cytoplasmic gamma-tubulin complex isolated from goat brain contains non-erythroid spectrin/fodrin. The major role of erythroid spectrin is to help in the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…The cell cycle dependent translocation of the c-TuRC to the centrosome in mammalian cells and the peculiar removal of the complex from the centrosome of post mitotic neurons point towards the existence of a stringent mechanism in place to cargo the c-TuRC to and from the MTOC in a temporally regulated fashion. Earlier studies reported by our group showed the colocalization of fodrin and the c-TuRC at the centrosome in brain-derived cells [13,14]. They were also found to be absent in the centrosome in primary neurons.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The cell cycle dependent translocation of the c-TuRC to the centrosome in mammalian cells and the peculiar removal of the complex from the centrosome of post mitotic neurons point towards the existence of a stringent mechanism in place to cargo the c-TuRC to and from the MTOC in a temporally regulated fashion. Earlier studies reported by our group showed the colocalization of fodrin and the c-TuRC at the centrosome in brain-derived cells [13,14]. They were also found to be absent in the centrosome in primary neurons.…”
Section: Discussionsupporting
confidence: 51%
“…Further immunocytochemistry studies in IMR-32 and U251 MG cells also showed the co-localization of c-tubulin with fodrin in centrosome. Moreover, immunoprecipitation experiment using purified centrosomes showed co-immunoprecipitation of fodrin with c-tubulin [14]. Given the apparent co-existence of fodrin and c-tubulin, we performed far western analysis using purified fodrin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using piggybac-mediated transgenesis methods, we generated TG pig lines harboring the target gene in the intron of CEP112 which encodes a centrosomal protein of 112 kDa and is localized around spindle poles, but its structure and function are still unclear (Jakobsen et al . 2011; Shashikala et al . 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a promising approach that can improve feed efficiency and reduce impacts on the environment is proposed. TG pig lines generated using PiggyBac-mediated transgenesis methods harbor the target gene in the intron of CEP112, which encodes a 112-kD centrosomal protein and is localized around spindle poles; however, the structure and function of the target gene remain unclear (Jakobsen et al 2011;Shashikala et al 2013). The pig lines in our study can efficiently express the foreign gene that can be stably inherited by the offspring, which exhibits normal and healthy performance whether it is heterozygote or homozygote.…”
mentioning
confidence: 98%